Relação nitrogênio e potássio em plantas de trigo irrigado cultivado no Cerrado Mato-Grossense - Freitas, Danityelle Chaves de (2016)
The Brazilian Cerrado is presented as an alternative for the production of wheat (Triticum aestivum L.) irrigated. The quality of the grain can be defined as a result of the management fertilization, soil fertility, climate and other factors edaphoclimatic. The objetive of the present study was evaluated the yield irrigated wheat grains, subjeted to combination of nitrogen dose and potassium in the fertilizer in two years in Mato-grossense Cerrado. The experiment was conducted in the field in Rondonopolis, Mato Grosso, in design of randomized blocks arranged in a factorial design 5x5, corresponding to five nitrogen doses: 0, 70, 140, 210, 280 kg ha-1 and five potassium doses: 0, 50, 100, 150 e 200 kg ha-1 . The plots were 12 m2 considering as a useful área 6,3 m2 . The irrigation was performed by means conventional sprinkler irrigation, whose management has been performed according to the climatic demand using the model of Penman Monteith. Were evaluated: Plants height, leaf number and tillers, chlorophyll index, leaf area index, lodging, spike number, yield, productivity, dry mass shoot and spike, thousand grain weight, hectoliter weight, falling number, concentration and accumulation of nitrogen in leaves and grain, concentration of potassium in the grains and crude protein. The data were analyzed of variance in response surface through the use of "Statistical Analysis System". Where the interaction was not significant, the study was conducted regression using the 5% significance level for all statistical tests. There was no significant interaction between the nitrogen and potassium for all variables studied in the two years of cultivation. The management with nitrogen fertilization and potassium fertilization influenced the development and production of wheat plants and the grains production in the first and second year cultivations in Mato-grossense Cerrado, the nitrogen range of 131,43 to 198,68 kg ha-1 and the potassium range of 83,83 to 179 kg ha-1 . Nitrogen and Potassium promoted increase in vegetative characteristics and yield grain, but potassium alone provided more yield of grains and better wheat industrial quality for the first year of cultivation.